Over 300 UMPSA students and staff celebrate the arrival of Kembara Sultan Pahang 1.0 - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 23 April 2025 – More than 300 students and staff of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) gathered to enliven the Kembara Sultan Pahang 1.0 Convoy Celebration as it passed through the UMPSA campus recently.